Real-World Analysis of Stroke Care: Thrombolysis and Thrombectomy in a Regional Stroke Unit in Germany - Christian Claudi; André Worm; Norma J. Diel; Martin Juenemann; Donata Schmohl; Hendrik Lösche; Hagen B. Huttner; Patrick Schramm (Emergency Care and Medicine)
Objectives: Stroke is a leading cause of disability worldwide, requiring timely intervention with intravenous thrombolysis (IVT) or endovascular thrombectomy (EVT). This study evaluates real-world stroke management in a regional stroke unit, focusing on IVT administration and EVT transfer logistics. Design: A sub-analysis was performed using prospectively collected data from an observational study. Setting: This study took place at a regional, non-university stroke unit in Germany, serving approximately 253,000 inhabitants. Participants: A total of 2436 patients were admitted for suspected stroke between May 2019 and June 2021. Outcome Measures: Outcome measures included IVT administration rates, reasons for IVT non-administration, and EVT transfer logistics for acute ischemic stroke (AIS) patients. Results: Of 952 stroke cases, 14.8% received IVT, with a mean door-to-needle time (DNT) of 41 ± 36 min. The most common reasons for IVT non-administration were unclear or elapsed symptom onset (51.8%), anticoagulation (7.9%), resolving symptoms (18.4%), and intracranial hemorrhage (7.1%). EVT transfers occurred in 6.7% of AIS patients, with a mean door-in-door-out (DIDO) time of 81 ± 36 min. Conclusions: This study highlights the low IVT rate, primarily due to delayed hospital presentation, and the limited number of EVT transfers. The prolonged DIDO times emphasize the urgent need for streamlined transfer protocols to optimize stroke care delivery.